KOMPILASI HUKUM ISLAM (KHI) DAN PENDAPAT MADZHAB SYAFI’I TENTANG BATASAN MASA TUNGGU SUAMI/ISTERI MAFQUD - Lestari, Novita Dwi (JURNAL ISLAM NUSANTARA, 2018)
mafqud is a person who has no news, unknown where it exists, whether alive or dead. Mafqud is one of the reasons for the divorce, which by court verdict contained in article 116 letter b Compilation of Islamic Law (KHI). in addressing mafqud matters KHI provides a limit waiting for 2 years, where as in the school of Shafi'i in qaul jadidnya give time for 90 years, and in his other opinion (qaul qadim) give a time limit for 4 years, then undergo iddah dead for 4 months and 10 days.